Contribution of public policies to the development of Colombian air transport - Díaz Olariaga, Oscar (2017)
Despite the dynamic growth experienced in the air transport sector in Latin America in general and Colombia in particular, there is a big gap in the scientific literature on the subject of public policies in the air transport sector and especially in the Colombian context. So this paper, of a descriptive character, develops, analyzes and evaluates how (through the analysis of several indicators) public policies contributed to the current development of air transport in Colombia.